A case of giant main pulmonary artery aneurysm associated with complicated congenital heart disease and simultaneous chronic pulmonary artery dissection - Wang, Yue-bo (J Cardiothorac Surg, 2020)
BACKGROUND: Pulmonary artery aneurysm (PAA), usually associated with congenital heart disease (CHD), is a very rare clinical condition. Pulmonary artery dissection (PAD) is considered the most life-threatening complication of PAA, and patients can progress from being asymptomatic to sudden death. We report the following case of PAA associated with complicated congenital heart disease and simultaneous chronic PAD. To our knowledge, few such complicated cases have ever been reported. CASE PRESENTATION: A 36-year-old male presented to our hospital with a 10-year history of heart fatigue after activities and aggravated for 2 years. Computed tomography angiography (CTA) and echocardiogram showed a giant main pulmonary artery aneurysm (14 cm) with complicated congenital heart disease (a small patent ductus arteriosus, ventricular septal defects, aortic coarctation). Chronic PAD, which was mistaken for a pulmonary valve before operation, was detected during surgery. CONCLUSIONS: PAA associated with complicated CHD and simultaneous PAD is very rare, and its clinical symptoms are varied. Radiologists and surgeons should pay attention to determining whether this patient simultaneously had PAD when PAA was detected on preoperative CTA imaging.